À la vie [videorecording (DVD)] - Zilbermann, Jean-Jacques; Depardieu, Julie, 1973-; Steege, Johanna ter; Clément, Suzanne (Breaking Glass Pictures, 2016)
Three Auschwitz survivors, and dear friends, meet again, against all odds. Inspired by a true story.